REARTICULATING THE ONTOLOGICAL ROOT OF CONTEMPORARY INDONESIAN CITIZENSHIP - Asri, Syamsul (JPP (Jurnal Politik Profetik), 2018)
This paper`s aim is to argue that citizenship could be been approached in the dialectical lens produced by creative antagonism between nation in one hand and state in other hand. This tension, if interrogated in postcolonial nuances, become the fertile habitus for Indonesian citizenry as creative and multilayered cross and inter-identity configuration, by which Indonesian exercise its rights and critical distance from both Indonesia as state (in terms of panoptical bureaucratic and enduring regime of political reservation)  and Indonesia as nation (in terms of myopic utopia spoken in language of impossibility as the main horizon bounding and creating togetherness of so called Indonesia) day by day. This rich notion of creative antagonism has embodiment in what been called as the surplus of aesthetic imagination explored by but not limited to Nirwan Ahmad Arsuka and DandhyLaksono (read as 2 temporary example of active citizenry of Indonesian) as exercise toward new horizon of what is possible to be Indonesian.